OMNICHANNEL CONSUMER BUYING BEHAVIOR: APPREHENDING THE PURCHASING PATTERN FOR MOBILE BUYERS IN INDIA - Sarika Kale, Nitin Zaware,Avinash Pawar, Harshada Samudre (International Journal of Advanced Science and Technology, 2020)
Today, the advancements of the Internet and new technologies have affected consumer behavior. This has led to the emergence of more and more channels which is causing consumers to change their purchasing habits. The omnichannel refers to retailers with a presence on both physical and digital platforms. It is a modern approach to commerce that focuses on designing a cohesive user experience for customers at every touchpoint. This paper deliberates on the omnichannel behavior of consumers in India towards the mobile phones. It analyses the channel preferences of mobile consumers, the selection of omnichannel during mobile purchase, and brand preferences in the omnichannel business environment. The outcome of this paper confirms that there is a significant relationship of socio-economic class with consumer information search, consumer evaluation of alternatives and consumer purchase decisions through online and offline sources which indicates the omnichannel behavior of consumer India for mobile products.